2020
DOI: 10.1038/s41598-020-70360-z
|View full text |Cite
|
Sign up to set email alerts
|

Programming experience associated with neural efficiency during figural reasoning

Abstract: In the present study, we investigated neural processes underlying programming experience. Individuals with high programming experience might develop a form of computational thinking, which they can apply on complex problem-solving tasks such as reasoning tests. Therefore, N = 20 healthy young participants with previous programming experience and N = 21 participants without any programming experience performed three reasoning tests: Figural Inductive Reasoning (FIR)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 82 publications
0
5
0
1
Order By: Relevance
“…The importance of the ability to critically evaluate the result obtained and to work in conditions of uncertainty of the future is substantiated by Hotyat (1952). Moreover, if applied correctly, this approach can qualitatively increase the efficiency of mastering the educational material and activate students' cognitive activity, and contribute to professional self-realization (Helmlinger et al, 2020).…”
Section: Analysis Of Foreign Studiesmentioning
confidence: 99%
“…The importance of the ability to critically evaluate the result obtained and to work in conditions of uncertainty of the future is substantiated by Hotyat (1952). Moreover, if applied correctly, this approach can qualitatively increase the efficiency of mastering the educational material and activate students' cognitive activity, and contribute to professional self-realization (Helmlinger et al, 2020).…”
Section: Analysis Of Foreign Studiesmentioning
confidence: 99%
“…Programming experience is also an influencing factor often considered in programming education. Helmlinger et al (2020) investigated the neural processes underlying programming experience and found that individuals with rich programming experience may develop a form of computational thinking. Master et al (2017) also pointed out that the lack of programming experience of young girls may be one of the main reasons for their less interest to participate in the fields of computer and engineering.…”
Section: Gender and Programming Experience In Programming On Ct Educa...mentioning
confidence: 99%
“…Programming experience is also an influencing factor often considered in programming education. Helmlinger et al. (2020) investigated the neural processes underlying programming experience and found that individuals with rich programming experience may develop a form of computational thinking.…”
Section: Gender and Programming Experience In Programming On Ct Educa...mentioning
confidence: 99%
“…Второй этап посвящен определению направлений учебно-познавательной деятельности по проектированию и разработке компьютерного игрового мира образовательного назначения инструментами языка программирования; максимально работающих на развитие навыков самостоятельного освоения новых технологий и оценивания их возможностей, взаимодействия в виртуальной игровой реальности, постоянного обновления знаний [23]. Соответствующая деятельность сопровождалась работой со сложными системами и большими объёмами данных.…”
Section: программа исследованияunclassified